Fiscal decentralization in the public sector of Lithuania: possibilities of development - Slavinskaite, Neringa; Davulis, Gediminas; PALECKIS, Kęstutis (International Journal of Contemporary Economics and Administrative Sciences, 2016)
The article deals with the possibilities to develop fiscal decentralization and the important part - the local tax authority in Lithuania. General principles of tax distribution on the state and local government levels are discussed. The situation in the sphere of the fiscal decentralization in Lithuania and the budget’s structure of Lithuanian municipalities from the point of view of fiscal decentralization is analyzed. The analysis showed, that non-tax income, which can be mostly influenced by local governments, comprises, but an insignificant share of all local governments income and its significance is not great. The local taxes do not play an important role in municipal budgets too, because these taxes comprise but a small share of municipal budgets. The volume of state subsidies for budgets of local authorities comprises more than a half of their total revenues. This fact testifies rather a low level of fiscal decentralization in the country. Similar situation is in the level of individual municipalities. The comparative analysis budget structures of the Vilnius and other capitals of Baltic countries showed that situation in Vilnius, Tallinn, Riga municipalities is similar and characterizes by low degree of financial independence of municipalities.